A bivalent live-attenuated vaccine candidate elicits protective immunity against human adenovirus types 4 and 7. Issue 1 (1st January 2021) - Guo, Jingao; Zhang, Youbin; Zhang, Yan; Zhang, Chao; Zhu, Caihong; Xing, Man; Wang, Xiang; Zhou, Dongming
ABSTRACT: Human adenovirus types 4 (HAdV4) and 7 (HAdV7) often lead to severe respiratory diseases and occur epidemically in children, adults, immune deficiency patients, and other groups, leading to mild or severe symptoms and even death. However, no licensed adenovirus vaccine has been approved in the market for general use. E3 genes of adenovirus are generally considered nonessential for virulence and replication; however, a few studies have demonstrated that the products of these genes are also functional. In this study, most of the E3 genes were deleted, and two E3-deleted recombinant adenoviruses (ΔE3-rAdVs) were constructed as components of the vaccine. After E3 deletion, the replication efficiencies and cytopathogenicity of ΔE3-rAdVs were reduced, indicating that ΔE3-rAdVs were attenuated after E3 genes deletion. Furthermore, single immunization with live-attenuated bivalent vaccine candidate protects mice against challenge with wild-type human adenovirus types 4 and 7, respectively. Vaccinated mice demonstrated remarkably decreased viral loads in the lungs and less lung pathology compared to the control animals. Taken together, our study confirms the possibility of the two live-attenuated viruses as a vaccine for clinic use and illustrates a novel strategy for the construction of an adenovirus vaccine.